Proteins are secreted by both constitutive and regulated secretory pathways in lactating mouse mammary epithelial cells (The Rockefeller University Press, 1992)
Lactating mammary epithelial cells secrete high levels of caseins and other milk proteins. The extent to which protein secretion from these cells occurs in a regulated fashion was examined in experiments on secretory acini isolated from the mammary glands of lactating mice at 10 d postpartum. Protein synthesis and secretion were assayed by following the incorporation or release, respectively, of [35S]methionine-labeled TCA-precipitable protein. The isolated cells incorporated [35S]methionine into protein linearly for at least 5 h with no discernible lag period. In contrast, protein secretion was only detectable after a lag of approximately 1 h, consistent with exocytotic secretion of proteins immediately after passage through the secretory pathway and package into secretory vesicles. The extent of protein secretion was unaffected by the phorbol ester PMA, 8-bromo-cAMP, or 8- bromo-cGMP but was doubled by the Ca2+ ionophore ionomycin. In a pulse- label protocol in which proteins were prelabeled for 1 h before a chase period, constitutive secretion was unaffected by depletion of cytosolic Ca2+ but ionomycin was found to give a twofold stimulation of the secretion of presynthesized protein in a Ca(2+)-dependent manner. Ionomycin was still able to stimulate protein secretion after constitutive secretion had terminated. These results suggest that lactating mammary cells possess both a Ca(2+)-independent constitutive pathway and a Ca(2+)-activated regulatory pathway for protein secretion. The same proteins were secreted by both pathways. No ultrastructural evidence for apocrine secretion was seen in response to ionomycin and so it appears that regulated casein release involves exocytosis. Ionomycin was unlikely to be acting by disassembling the cortical actin network since cytochalasin D did not mimic its effects on secretion. The regulated pathway may be controlled by Ca2+ acting at a late step such as exocytotic membrane fusion.